2006
DOI: 10.1007/s10916-006-7406-z
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of HIPAA Regulation to Implementation of Health Services Research

Abstract: Although many perspectives on the impact of the Health Insurance Portability and Accountability Act of 1996 (HIPAA) on health services research have been wide spread, little empirical evidence has been reported about HIPAA-related barriers during the implementation of research projects. Using three cases of health services research projects, this study examined practical barriers created by HIPAA regulation. During the stage of implementation of the three projects, we experienced some HIPAA-related concerns, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…More importantly, about 39% of researchers believed HIPAA had increased research cost by a great deal, especially due to additional compliance related administrative cost and about 51% of researchers believed HIPAA enforcement lead to inadvertent delays in research. In a critical review of three cases of health research projects, Shen et al (2006) report that the complexity of consent forms and privacy protection forms, time consuming and cost amplifying procedures often get in the way of patient recruitment. The authors recommend simplifying the language of privacy and consent forms to facilitate easier comprehension by patients.…”
Section: Providers' Perspective Of Regulatory Compliancementioning
confidence: 99%
“…More importantly, about 39% of researchers believed HIPAA had increased research cost by a great deal, especially due to additional compliance related administrative cost and about 51% of researchers believed HIPAA enforcement lead to inadvertent delays in research. In a critical review of three cases of health research projects, Shen et al (2006) report that the complexity of consent forms and privacy protection forms, time consuming and cost amplifying procedures often get in the way of patient recruitment. The authors recommend simplifying the language of privacy and consent forms to facilitate easier comprehension by patients.…”
Section: Providers' Perspective Of Regulatory Compliancementioning
confidence: 99%
“…26,27 Alternative means of achieving meaningful protection of participant privacy in research have been proposed. 18,20,28,29 The findings of this and other studies warrant further investigation of the impact of inclusion of HIPAA authorization in the informed consent process and evaluation of other means of achieving privacy protections. Given the present federal and institutional requirements to include HIPAA authorization as part of the informed consent process, these types of studies may be difficult to conduct, as has been described.…”
Section: Discussionmentioning
confidence: 66%
“…A case study examining the consent process finds that technically complicated consent and privacy protection forms were a main factor preventing research participation. 20 Two published studies that compared the proportion of eligible individuals who consented to enroll in a research pre-and post-implementation of privacy legislation found a significant decrease in recruitment and an effect upon generalizability. 21,22 Neither of these studies examined individuals' reasons for declining to participate.…”
Section: Introductionmentioning
confidence: 99%
“…Gaining permission from individuals to gather these types of data is difficult, in part because of the publicity surrounding the implementation of privacy rules and the mis-interpretation of the requirements by providers. Researchers have reported that the requirements for informed consent and the explanation of risks has reduced individuals' willingness to participate in research and concerns over penalties for disclosure of information have made organizations reluctant to make data available to researchers [16]. These changes may result in fewer research studies or research studies that are less scientifically robust.…”
Section: General Issuesmentioning
confidence: 99%
“…16 The opportunity is clear from the way in which ubiquitous information technologies has transformed many facets of human interaction and organization. Tools such as the Grid, MySpace, and Second Life have changed how people congregate, collaborate, and communicate.…”
Section: Utility Confidentialitymentioning
confidence: 99%